The Quality of Chinese PhDs: Achievements, Problems and Responses. Issue 3 (4th May 2018) - Chen, Hongjie; Zhao, Shikui; Shen, Wenqin; Cai, Leiluo
Abstract: The study finds that after 30 years of effort, China has gradually built a doctoral education and quality assurance system with Chinese characteristics and realized its strategic goal of training high-level talents based in China. The survey and bibliometric analysis show that the relevant groups are satisfied with the training of Chinese PhD students. Doctoral dissertation topics are on the leading edge, referenced works are relatively complete, the writing is fairly standardized, the research results are comparatively innovative, and the overall Chinese PhD quality is gradually approaching international levels. PhD students have already become an important force in academic paper production. However, Chinese doctoral education still has numerous problems, such as serious loss of outstanding student sources, differences in the quality of doctoral dissertation from varying institutions, and remaining gaps in innovative ability compared with global higher education superpowers. Policies should be adopted to increase the strategic position of Chinese doctoral education, improve the doctoral education quality assurance system, and strengthen the capability of doctoral education to adapt to socioeconomic development.